Authentic leadership and employee silence intention: Mediated by perceptions of organizational politics and organizational commitment - Sumarmi Saptaningsih; Muchran Murniady; Sudaryana Arif (Journal of Economics and Management)
Aim/purpose – This study examines authentic leadership’s influence on employee silence intention, mediated by perceptions of organizational politics and organizational commitment.